Promoting Developmental Outcomes of Premature Infants by Creating Opportunities for Parent Empowerment (COPE) - Narges Shafaroodi; Reihaneh Askary Kachoosangy; Mohammad Heidarzadeh; Mostafa Qorbani; Seyed Hossein Shojaei; Seyede Zeinab Beheshti (Iranian Rehabilitation Journal, 2022)
Objectives: Premature neonates are at greater risk of developmental problems such as cerebral palsy, developmental delays, and hearing and vision problems. The challenge of healthcare professionals who support preterm neonates and their parents is not only ensuring neonates’ survival but also optimizing infant development. Interventions to reduce adverse health outcomes are very important. The present study was focused on exploring the effect of the Creating Opportunities for Parent Empowerment (COPE) schedule on the developmental outcomes of premature infants Methods: The randomization process was done using a randomized block design, and neonates were assigned randomly to the treatment (n=20) and control (n=20) groups. Neonates in two groups were matched in gestational age, birth height, head circumference at birth, birth weight, Apgar scores (1 min, 5 min), prematurity, and new Ballard score. So, there was not a significant difference between them at the baseline. In the intervention group, the parents received a COPE schedule in a set of CD’s in conjunction with written instruction and supplemental activities (guidebook). COPE schedule was performed in 5 steps. In the control group, neonates received only routine services and interventions, and the research therapist performed no additional interventions. New Ballard examination was done in all neonates at the time of enrollment, followed by administration of Ages and Stages Questionnaire (ASQ) by an occupational therapist, who was double-blinded for the study, to any available parent (mostly mothers) at 6 months of corrected age. Results: The results showed more maturity in “communication”, “gross motor”, “problem-solving”, and “personal-social” in the intervention group, and the observed differences between the two groups in these outcomes were statistically significant (P<0.05). Discussion: This educational-behavioral intervention program could promote mothers’ knowledge about their neonates and improve the developmental aspects of premature infants during their first months of life.